The Content of Essential and Toxic Metals in the Hair of Children with Autistic Spectrum Disorders - Pilić, Selma; Kalić, Erna; Selović, Alisa (Bulletin of Chemists and Technologists of Bosnia and Herzegovina, 2021)
The aim of this study was to assess the possible relationship between the content of essential and toxic metals in the hair samples with the etiology of autism spectrum disorder (ASD) in children from Bosnia and Herzegovina. Taking into account the age and gender of the child, in the study and control group, the samples were divided into three subgroups (1-5 years; 6-9 years; 10-14 years). Altered profiles of the values of the Cu, Fe, Mn, Zn, Cd, Co, Cr, Ni, Pb in the study group were observed in comparison with the control group children with typical neuromotor development. Higher values of toxic metal concentrations (Co, Ni, Cd, Pb) were found in boys, compared to the girls in the study group. The content of Pb in the study group was higher in all three ages compared to their controls, with the difference being especially pronounced in the age group 1-5 years (6.64 mg/kg; 1.89 mg/kg). A strong correlation between the content of Pb and Cd (0.93) was confirmed. Lower values of Cr concentration and higher of Ni, Cu and Fe were recorded in the study group. Statistically significant differences (p<0.05) were found in Zn concentrations (6-9 years; 10 -14 years) between the control and study groups. The findings help highlight the role of heavy metals as environmental factors in the etiology of ASD.